Long-term effects of perinatal exposure to low doses of cadmium on the prostate of adult male rats - Santana, Viviane P. [UNESP]; Salles, Évila S.; Correa, Deborah E.; Gonçalves, Bianca F. [UNESP]; Campos, Silvana G. [UNESP]; Justulin, Luiz A. [UNESP]; Godinho, Antonio F. [UNESP]; Scarano, Wellerson R. [UNESP] (Wiley, 2016)
Developmental toxicity caused by environmental exposure to heavy metals during the perinatal period has raised questions about offspring health. Cadmium (Cd) is an endocrine-disrupting chemical with the potential to interfere with morphogenesis and susceptibility to diseases in reproductive organs. Taking into account that in the rat prostate morphogenesis occurs during the perinatal period, and that pregnant females absorb and retain more dietary Cd than their non-pregnant counterparts, it is important to understand the effects of perinatal Cd exposure on the adult rat prostate. Therefore this study investigated the effects of gestational and lactational Cd exposure on adult offspring rat prostate histopathology. Pregnant rats (n = 20) were divided into two groups: Control (treated with aqueous solution of sodium acetate 10 mg/l) and treated (treated with aqueous solution of cadmium acetate 10 mg/l) administered in the drinking water. After weaning, male offspring from different litters (n = 10) received food and water ‘ad libitum’. The animals were euthanized at postnatal day 90 (PND90), the ventral prostates (VPs) were removed, weighed and examined histopathologically. Blood was collected for the measurement of testosterone (T) levels. Immunohistochemistry for androgen receptor (AR) and Ki67, and a TUNEL assay were performed. There were no differences in T levels, cell proliferation and apoptosis indexes, or AR immunostaining between the experimental groups. Stromal inflammatory foci and multifocal inflammation increased significantly in the treated group. These changes were associated with inflammatory reactive epithelial atypia and stromal fibrillar rearrangement. In conclusion, VP was permanently affected by perinatal Cd exposition, with increased incidence of inflammatory disorders with ageing.
Keywords: cadmium; perinatal exposure; prostate; rat